Chemical drug design - Gupta, Girish Kumar; Kumar, Vinod (Professor of chemistry) (Walter de Gruyter GmbH & Co., KG, 2016)
Chemical Drug Design provides a compact overview on recent advances in this rapidly developing field. With contributions on in silico drug design, natural product based compounds, as well as on ligand- and structure-based approaches, the authors present innovative methods and techniques for identifying and synthetically designing novel drugs.